Employee Overtime Administration Information System at Production Division 3 PT. Konimex Indonesia: Sistem Informasi Administrasi Lembur Pegawai Pada Divisi Produksi 3 PT. Konimex Indonesia - Putranto, Khodim Ridwan Firdaus; Naafian, Nuur Rochman; Wibowo, Kresno Ario Tri (Politeknik Harapan Bangsa Surakarta, 2023)
Production division of PT. Konimex Indonesia has problems in terms of collecting data on employee overtime hours. This happens because the data collection process is still carried out using notebooks that cause problems, including book media that is easily lost and damaged. The process of collecting overtime hours is also a problem because data collection and counting of hours are still carried out by recording directly in the employee's overtime logbook. In addition, the payroll administration department also has difficulties in the process of preparing employee overtime data reports. Based on these problems, the author formulates a problem, namely how to design and create an employee overtime administration information system. The author gives a limit on this study, which only discusses the payroll system in the production division of 3 PT. Konimex Indonesia. The system inputs that the author discusses are employee data and overtime data. The system output that the author discusses is an employee overtime data report. The author uses the SDLC (System Development Life Cycle) method in the information system developer method. The information system is designed and created using the PHP programming language and the MyQL database. The author's goal in this study is to create an information system for the administration of employee overtime data in the production division that can be used by the administration to process overtime data up to the report creation process.